Moose (Alces americanus) habitat suitability in temperate deciduous forests based on Algonquin traditional knowledge and on a habitat suitability index. Issue 3 (1st October 2016) - Tendeng, Benoît; Asselin, Hugo; Imbeau, Louis
ABSTRACT: Traditional ecological knowledge (TEK) garners increasing attention in science-based wildlife management. We used the TEK of 16 First Nation hunters from the Eagle Village Algonquin community (Quebec, Canada) to evaluate moose ( Alces americanus ) habitat suitability in temperate deciduous forests, compared with a habitat suitability index (HSI) model. We found moderate to strong agreement between TEK and the HSI using Cohen's kappa (κ = 0.46–0.63). According to the Algonquin hunters, wetlands and lakes are frequented by moose to feed and to avoid temperature stress during warm summer days, something not taken into account by the HSI. Algonquin hunters also mentioned that unproductive areas are actively frequented by moose in the summer and during the rutting period, although they have a low weight in the HSI calculation. Also according to Algonquin hunters, mature coniferous stands and large-size regenerating areas are rarely used by moose. While the moose HSI model was developed in boreal mixed and coniferous forests, we have shown that it could also be used in temperate deciduous forests. It could be improved, however, to better correspond to TEK, notably by including wetlands and lakes, increasing the weight of unproductive stands and reducing weights of mature coniferous and regenerating stands.